Nilai-Nilai Pendidikan Karakter Melalui Program Boarding School di MAN 1 Lampung Barat - Karmilah Karmilah; Heru Juabdin Sada; Muhammad Mustofa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Character education is a process by which a nation prepares its nation's generation to be able to achieve a quality life. Related to this problem needs to be researched where this study is about: the values of character education through the Boarding School program at MAN 1 West Lampung. With the formulation of the problem, namely: first, what are the values of character education developed in the boarding school program at MAN 1 West Lampung? Second, what are the supporting and inhibiting factors in the application of character education values in MAN 1 West Lampung? The method in this study is qualitative research using a descriptive approach. Data collection techniques used include observation, interviews, and documentation. From this study, several conclusions were produced about character education at MAN 1 West Lampung Boarding School, namely: the values of character education contained include religious character, honesty, tolerance, discipline, hard work, creativity, independence, friendly or communicative, responsibility and care for the environment. There are supporting and inhibiting factors in the application of environment. There are supporting and inhibiting factors in the application of character education values, these factors include internal factors such as innate and personality, as well as external factors such as family, friends, and the surrounding environment.